2019
DOI: 10.1039/c9gc01811e
|View full text |Cite
|
Sign up to set email alerts
|

A copper-catalyzed diastereoselective O-transfer reaction of N-vinyl-α,β-unsaturated nitrones with ketenes into γ-lactones through [5 + 2] cycloaddition and N–O bond cleavage

Abstract: A copper-catalyzed atom economical O-transfer reaction strategy was developed for the synthesis of densely functionalized γ-lactones from N-vinyl-α,β-unsaturated nitrones and ketenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Due to weak N-O σ bonds [ 5 ], the average energy of about 57 kcal/mol −1 , is far below the σ C-X (X = C, N, O), thus N-O bond units have been considered to be quite unstable bonds. Those N-O bond compounds are easy to break under the influence of a transition-metal catalyst, transition-metal-free catalyst, or photocatalyst, allowing the formation of new C-N, C-O, or C-C bonds to build nitrogen compounds (e.g., nitrogen-containing heterocycles [ 5 , 6 , 7 , 8 , 9 ], alkyl nitriles [ 10 , 11 , 12 ], and amines [ 13 ]), or oxygen-containing compounds [ 14 , 15 , 16 , 17 , 18 ]. Reactions involving N-O bond cleavage have a long history in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to weak N-O σ bonds [ 5 ], the average energy of about 57 kcal/mol −1 , is far below the σ C-X (X = C, N, O), thus N-O bond units have been considered to be quite unstable bonds. Those N-O bond compounds are easy to break under the influence of a transition-metal catalyst, transition-metal-free catalyst, or photocatalyst, allowing the formation of new C-N, C-O, or C-C bonds to build nitrogen compounds (e.g., nitrogen-containing heterocycles [ 5 , 6 , 7 , 8 , 9 ], alkyl nitriles [ 10 , 11 , 12 ], and amines [ 13 ]), or oxygen-containing compounds [ 14 , 15 , 16 , 17 , 18 ]. Reactions involving N-O bond cleavage have a long history in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrones, as extensively used 1,3-dipoles, have served as powerful reagents to access various significant azaheterocycles by cycloaddition reaction . In recent years, N -vinyl nitrone has been received much attention because of their ease in further transformations, such as electrocyclization, O -transfer reaction, and cycloaddition reaction . Based on the studies of N -vinyl nitrones in our group, we found that N -vinyl-α,β-unsaturated nitrones could participate in cycloaddition/rearrangement to access nine-membered azahetereocycles by reacting with various electrophiles .…”
mentioning
confidence: 99%
“…6 The oxygen transfer reaction of nitrones could offer various useful building blocks. 7 Recently, N -vinyl nitrones have gained much attention in organic synthesis owing to their rich chemical transformations of the double bond on the N-atom, such as [3 + 2], [3 + 3], [4 + 1], [4 + 2], or [5 + 2] cycloadditions and intramolecular cyclization. 8 For example, Anderson's group developed a 4π-electrocyclization of malonoate-derived N -alkenyl nitrones or 6π-electrocyclization of β-keto ester-derived N -alkenyl nitrones to afford azetide nitrones and unsaturated morpholines, respectively (Scheme 1A).…”
mentioning
confidence: 99%